Rapid resolution of a third nerve palsy from pituitary apoplexy - Hanna, Verina (BMJ Case Rep, 2021)
A 49-year-old man presented with new onset headache and diplopia, with right ptosis and limitation of extraocular movements consistent with a third nerve palsy. He had a known diagnosis of a non-functioning pituitary adenoma, and his presentation and neuroimaging were consistent with ischaemic pituitary apoplexy. The patient was otherwise stable with no signs of optic neuropathy or endocrine abnormality. He was observed with close interval follow-up and reported resolution of symptoms within 4 days after onset. Pituitary apoplexy is a potentially life-threatening condition often managed with initial medical stabilisation followed by neurosurgical decompression. The guidelines regarding the utility of surgery in patients with isolated ocular motility disorders are unclear, and recent retrospective studies suggested that outcomes may be similar in patients managed conservatively. This case demonstrates that rapid resolution of an isolated third nerve palsy may occur in this setting, and that observation is a reasonable initial management strategy.